Exercise engagement drives changes in cognition and cardiorespiratory fitness after 8 weeks of aerobic training in sedentary aging adults at risk of cognitive decline - Hinchman, Carrie A.; Cabral, Danylo F.; Ciesla, Marissa; Flothmann, Marti; Nunez, Christina; Rice, Jordyn; Loewenstein, David A.; Kitaigorodsky, Marcela; Cahalin, Lawrence P.; Rundek, Tatjana; Pascual-Leone, Alvaro; Cattaneo, Gabriele; et al. (Frontiers in Rehabilitation Sciences, 2022)
Background With our aging population, many individuals are at risk of developing age-related cognitive decline. Physical exercise has been demonstrated to enhance cognitive performance in aging adults. This study examined the effects of 8 weeks of aerobic exercise on cognitive performance and cardiorespiratory fitness in sedentary aging adults at risk for cognitive decline. Methods Fifty-two participants (age 62.9 ± 6.8, 76.9% female) engaged in eight weeks of moderate-to high-intensity exercise (19 in-person, 33 remotely). Global cognition was measured by the Repeatable Battery for the Assessment of Neuropsychological Status, the Delis-Kaplan Executive Function System, and the Digit Span subtest of the Wechsler Adult Intelligence Scale (WAIS) Fourth Edition. Cardiorespiratory fitness was measured via heart rate recovery at minute 1 (HRR1) and 2 (HRR2), and exercise engagement (defined as percent of total exercise time spent in the prescribed heart rate zone). We measured pre and post changes using paired t-tests and mixed effects models, and investigated the association between cardiorespiratory and cognitive performance using multiple regression models. Cohen's d were calculated to estimate effect sizes. Results Overall, 63.4 % of participants demonstrated high engagement (≥ 70% total exercise time spent in the prescribed heart rate zone). There were significant pre-post improvements in verbal fluency and verbal memory, and a significant decrement in working memory, but these were associated with small effect sizes (Cohen's d <0.5). Concerning cardiorespiratory fitness, there was a pre-to-post significant improvement in HRR1 (p = 0.01, d = 0.30) and HRR2 (p < 0.001, d = 0.50). Multiple regressions revealed significant associations between cardiorespiratory and cognitive performance, but all were associated with small effect sizes (Cohen's d < 0.5). Interestingly, there were significant between-group differences in exercise engagement (all p < 0.001), with remote participants demonstrating greater exercise engagement than in-person participants. Conclusion Improvements in cognition and cardiorespiratory fitness were observed after 8 weeks of moderate to high-intensity exercise in aging adults. These results suggest that committing to a regular exercise regimen, even for a brief two-month period, can promote improvements in both cardiorespiratory fitness and cognitive performance, and that improvements are driven by exercise engagement.